Diagnosis of Enteric Fever Cases: Current Challenges of Azithromycin Resistant R717Q Gene in Rajshahi, Bangladesh - Sazzad, Jarin; Alam, Md Shah; Das, Haimanti Shukla; Rahman, Nahreen; Haque, Quazi Tamanna; Rahman, Kazi Mohaimenur (TAJ: Journal of Teachers Association, 2023)
Salmonella enterica serovars typhi is a contributing typhoid agent, leading to untreatable infections based upon the rising prevalence of antimicrobial resistance in the said agent. Consequently, the main concern of the health service providers to treat expansively drug-resistant (XDR) enteric fever has been dependent on the only remaining oral drug, Azithromycin, for creating emerging resistance against it. Therefore, a cross-sectional descriptive study was conducted in the Microbiology Department of Rajshahi Medical College, Rajshahi, to identify Salmonella species by Fastidious Antibiotic Neutralization (FAN) method in suspected enteric fever cases along with its antimicrobial susceptibility pattern and molecular detection of Azithromycin resistant R717Q gene. Samples were collected purposively. Regarding the population's age distribution, out of 127 specimens, the predominant 37(29.1%) were found within the age group of 35-44 years. Automated blood culture was found positive in 64(50.39%) population; out of them, Salmonella spp were 38(59.37%) of the population. Among them 29(76.31%) have travel history, took street food 25(65.7%), used tap water for drinking 21(55.2%) and had kancha latrine 24(63.1%). It was found that 18.43% were sensitive and 81.57% resistant to Azithromycin. Azithromycin-resistant Salmonella spp. were detected in 31(81.57%), and among Azithromycin resistant R717Q gene was identified in 9(29.03%). The azithromycin-resistant R717Q gene was identified by conventional PCR. Because of its oral course of administration, Azithromycin is considered the widely used drug in Bangladesh, which is used once on a dose basis a day. In order to contribute to the development of this drug resistance, there could be many reasons, and among them there are the availability over the counter and the imperfectly done treatment. Thus, this study would be helpful to formulate a regional hospital empirical therapy by antimicrobial sensitivity and resistance pattern of the gene for Azithromycin resistance in Rajshahi Medical College Hospital. TAJ 2022; 35: No-2: 67-73